Pengaruh Komisaris Independen, Financial Distress Dan Audit Report Lag Terhadap Integritas Laporan Keuangan - Teti duwi astuti; Yunita kurnia shanti (CV. ITTC INDONESIA, 2026)
This study aims to explain and provide empirical evidence regarding the influence of independent commissioners, financial distress, and audit report lag on the integrity of financial statements. The research was conducted by analyzing the financial statements of companies in the healthcare sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sample consists of 11 healthcare companies selected using a purposive sampling technique. The data used in this study are secondary data in the form of annual reports of each sampled company.